Rational use of chloroquine and hydroxychloroquine in times of covid-19 - Lucchetta, Rosa Camila [UNESP] (2019)
Considering the COVID-19 pandemic declared, part of the researchers’ efforts has been in studies of repurposing chloroquine (CQ) and hydroxychloroquine (HCQ), cheap medicines that have been used for decades with indication for malaria, rheumatoid arthritis and systemic lupus erythematosus. Chinese and South Korean health officials recommended the use of QC and HCQ for prophylaxis and treatment of COVID-19, encouraging researchers around the world to assess the potential of these medicines as antivirals. To date, results of three clinical trials have been released. Two studies show divergent results for virological clearance, while the third suggests a benefit in terms of radiological and clinical improvement. The three studies have methodological limitations and low overall quality of evidence, in view of the absence of randomization, allocation concealment, blinding patients, health care providers, and outcome assessors, missing data and/or selective reporting of results, as well as probable heterogeneity of patients and treatments, imprecision due to the reduced statistical power of the studies, indirect evidence for patients with severe form of the disease or patients with high severity comorbidities. The irresponsible self-medication of these medicines is of concern both for the potential risk of shortages, as well as for the adverse events and potentially fatal intoxications. Thus, in the USA, Europe and Brazil, regulatory agencies have positioned themselves in an emergency, authorizing the use of CQ and HCQ under medical criteria and/or in the context of clinical trials. In Brazil, to restrict irresponsible self-medication and possible shortages, Anvisa included the drugs in a special control list. Evidence on the efficacy and safety of QC and HCQ remains uncertain, so the results of ongoing studies are needed to adequately guide public policy and clinical practice. Evidence-based health assumptions must be maintained even in times of international emergency due to the risk of having to deal with future complications from the irrational use of these medicines.